(untitled) (Research Announcements "Heritage BG", 2025)
Analyzing street name changes in comparative perspective in Southeast Europe in the context ofdeep political changes after 1989, the article underlines the significance of this underexplored aspect of symbolic politics. In addition, the article explores the Sofia case through less known archival material. The article shows a break with the pre-1989 model as part of processes of de-communization in the cases of Bucharest and Sofia, with the Romanian capital being characterized with more radical and rapid change. The article shows that in spite of popular perceptions for massive street names change in Sofia directly after 1989 in fact the process of large-scale renaming took place later during the second post-communist administration. In the case of Belgrade, the urban landscape was redesigned later and just a part of the urban symbolic landscape underwent some reassessment. References: Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 469, 67-88, 105-106. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 471, 99-101. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 472. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 477. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 478. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 625, 13-17. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 626. Bulgarian State Archive, Regional Archive – Sofia, fond 65, op.15, a.e. 628, 147-148. Light, Duncan (2004). Street Names in Bucharest, 1990–1997: Exploring the Modern Historical Geographies of Post-socialist Change. - Journal of Historical Geography, No. 30, 154-172. Light, Duncan, Young, Craig (2014). Habit, Memory, and the Persistence of Socialist-Era Street Names in Postsocialist Bucharest, Romania. - Annals of the Association of American Geographers, No.3, 668-685. Radović, Srđan (2008). From Center to Periphery and Vice Versa: The Politics of Toponyms in the Transitional Capital. - Гласник Етнографског института САНУ, No. 2, 53-74.